Protection of Human Rights in the UN from a Central European and Certain Eastern European States’ Perspective - Oręziak, Bartłomiej (The Universal Protection of Human Rights, 2026)
Abstract: This chapter will conduct a comparative analysis of the protection of human rights within the framework of the United Nations (UN) for 16 countries. The primary aim of the study is to identify similarities and differences in the approaches of Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Czech Republic, Georgia, Hungary, Moldova, Montenegro, North Macedonia, Poland, Romania, Serbia, Slovakia, Slovenia, and Ukraine to the UN human rights protection system, including the implementation of international obligations arising from it. This overarching goal determines the subsidiary objectives of the study. First, the study will explore the historical development of human rights in the analysed countries. Second, it will examine the relationship or stance of the selected countries toward the UN from a human rights perspective. Third, it will analyse the scope of international obligations undertaken by the selected countries, identifying which UN human rights conventions each country is a State Party to. Fourth, the study will focus on the process and timeline of ratification, accession, or succession to the key UN human rights conventions. Fifth, it will assess the impact of these international legal acts on the domestic legal systems of the analysed countries. Sixth and finally, the study will review cases involving the analysed countries brought before UN treaty bodies concerning these key UN human rights conventions. The chapter will conclude with a consolidated presentation of all 16 countries in a single summary, finalising the study’s primary objective.Keywords: Human Rights, United Nations, Central Europe, Eastern Europe, Comparative Law